2021
DOI: 10.1080/1331677x.2021.1875255
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional decision with nested probabilistic linguistic term sets and its application in corporate investment

Abstract: With the rapid development of information, decision making problems in various fields have presented multidimensional, complex and uncertain characteristics. Nested probabilistic-numerical linguistic term set (NPNLTS) is an effective tool to describe complex information due to the nested structure and diverse variables. This paper extends the concept of NPNLTS, and defines an improved form, i.e., nested probabilistic linguistic term set (NPLTS), and then proposes a novel VIKOR method with nested probabilistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The researchers presented a case study of corporate investment, which is based on the proposed new VIKOR method with nested probabilistic linguistic information. Wang et al ( 2021 ) used the VIKOR method with the nested probabilistic linguistic term set (NPLTS) to study how firms improve their investment decisions.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…The researchers presented a case study of corporate investment, which is based on the proposed new VIKOR method with nested probabilistic linguistic information. Wang et al ( 2021 ) used the VIKOR method with the nested probabilistic linguistic term set (NPLTS) to study how firms improve their investment decisions.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Obviously, HFLTS cannot meet the needs of DMs. In contrast, multi-granularity probabilistic linguistic term set (MGPLTS) (Liu et al, 2021) provides linguistic terms with different granularity levels (similar to Likert scale of different levels) and corresponding probability values, which not only takes into account the advantages of probabilistic linguistic term set (Pang et al, 2016;Wang et al, 2021b), but also reflects the linguistic preference of DMs. For example, the evaluation information from DM e 1 is {l 1 5 (0.7), l 2 5 (0.3)}, and the evaluation information from DM e 2 is {l 2 7 = very good (0.5), l 3 7 = extremely good (0.5)}.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2020) provided a multi-stage medical scheme selection process related to referral system under probabilistic linguistic environment. Wang et al (2021) developed a multi-dimensional methodology with nested PLTSs and applied it to corporate investment. Xue et al (2021) demonstrated a dynamic reference point method with probabilistic linguistic information based on the regret theory for public health emergency decision-making.…”
Section: Introductionmentioning
confidence: 99%